Intelligent home automation system (IHAS) with security protection - Neo, Chan Loong (2016)
This project paper presents the overall implementation design of the cost effective and high efficiency system of Intelligent Home Automation System (IHAS) with Security Protection. This framework is designed to fulfil the needs of busy life of the owner, the elderly and the handicapped at house to control and receive home information and emergency security respond at anytime and anywhere the owner is. The technology of Internet of Things (IoTs) will allows the user to receive and to realize the home condition from the internet with any electronic devices that capable to access to the internet. The owner will get notified once the security protection system detects unauthorized access to the house. Besides, the idea concept of the intelligent home automation system also will improve the standard living status at house. This allows the user to control their home electrical appliances automatically without manually control. The system design also does not remove the existing switches but it will provide safer control over all of the switches with low voltage electronic usage technique. In addition, with the use of intelligent home automation system, it will be more effective when the security protection is implemented. When unauthorized access happen in the house or the theft try to break into the house, sensors will detect and process by notifying the user immediately and trigger the alarm as well. With combination of both Intelligent Home Automation System and Security Protection implement, generally the system is designed intended to control the electrical devices throughout the house and protecting the house invisibly with relatively low cost design, ease of installation and user friendly interface.